Price transmission on agricultural markets: methodological approaches - S. V. Kharin (Аграрная наука Евро-Северо-Востока)
The phenomenon of price transmission on various agricultural markets has attracted the attention of scientists in the 21-st century. Empirical studies of price relationships at various market levels can be found in recent publications. In this scientific review the survey was carried out as to the existing empirical literature on price transmission in agricultural markets of European, Asian, North and South American countries. The paper also presents the analysis of the most important methodological approaches, which are very heterogeneous in the aspects of econometric models, asymmetry types and empirical results. The article provides a detailed analysis of applied research in the field of the linear and nonlinear concepts of cointegration, also the most popular econometric price transmission models have been assessed in the light of the main advantages and disad-vantages with a special focus on autoregressive models with distributed lags, error correction models, nonlinear models with switching regimes and vector autoregressive models. In recent years nonlinear and nonparametric methodological approaches and techniques have become widely used in applied research of market integration and price transmission.